Neonatal Infections Pathophysiology, Diagnosis, and Management (Springer International Publishing, 2018)
This book is designed to succinctly cover the pathophysiology, epidemiology, clinical presentation, diagnosis and treatment, and important aspects of preventative care for the most frequently encountered neonatal and congenital infections. The first section discusses common neonatal infections acquired during or after delivery, including sepsis, meningitis, necrotizing enterocolitis, and other focal infections. The second section covers a wide range of congenital infections including cytomegalovirus, hepatitis, syphilis, and HIV. The final section discusses the basics of infection prevention, outbreak management, antibiotic stewardship, and immunizations in the nursery setting. Written by an expert in infectious diseases and neonatal/perinatal medicine, this book is the only resource focused exclusively on newborns that is both current and easily accessible. Handbook of Neonatal Infections is an excellent resource for infectious disease specialists, neonatologists, pediatricians, family practitioners, medical students, hospitalists, nurses, and all clinicians caring for infants in the nursery or neonatal intensive care unit.